Cost-Benefit Analysis of Kirkuk Sulymaniya Railway Project - Ali J. Kadhim; Mohmmad B. Abdljabar; Shatha S. Kareem (Journal of Engineering and Sustainable Development, 2013)
The railway network is considered one of the major stone in the economic skeleton in most countries. Herein, the user benefit was investigated when a new railway track is to be installed between Kirkuk and Sulymaniya cities in the north of Iraq. The operating costs of the new railway line are compared with the existing transportation modes that depend only on multilane highway between the two cities. The analysis was done using the related parameters that involved in the cost benefit procedures, beside that this project have the ability of joining Iran with Iraq and consequently joining the Iraqi railways. The results show that when the construction and other initial costs are added the economic evaluation is negative and results no user benefit, while in the real world there are impacts on the development of the society when such transportation projects are installed. This paper concluded that there is a great user benefit in the proposed project when the operating, accidents, time saving costs and the ecological effects are considered, with the excluding of the initial costs as in the case of the roadway construction.